2009
DOI: 10.1111/j.1365-3156.2009.02371.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to chemical insecticides of two Brazilian populations of the visceral leishmaniasis vector Lutzomyia longipalpis (Diptera: Psychodidae)

Abstract: Summaryobjectives To investigate the insecticide susceptibility of two geographically separated Lutzomyia longipalpis populations (Lapinha and Montes Claros) with different histories of insecticide exposure (i.e. no exposure and repeated exposure, respectively).methods (i) Bioassay monitoring of sand fly survival over time when exposed to a range of insecticides; and (ii) analysis of the level of insecticide detoxification enzymes in individual sand flies caught at both study sites. Insecticides tested were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 8 publications
4
52
0
3
Order By: Relevance
“…There is an urgent need to establish the susceptibility status of the Indian vector to a range of insecticides that could potentially be used as alternatives to DDT for IRS (47). Susceptibility to deltamethrin and organophosphates has been claimed (27); however, the numbers of insects tested in these studies are low.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to establish the susceptibility status of the Indian vector to a range of insecticides that could potentially be used as alternatives to DDT for IRS (47). Susceptibility to deltamethrin and organophosphates has been claimed (27); however, the numbers of insects tested in these studies are low.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not test for such additional indirect impacts; however, preliminary data indicate a reduction in the feeding success of exposed IR mosquitoes. In this and other studies (30,31), it was observed that the legs of mosquitoes can become detached when trying to feed through nets, which would be one mechanism to explain their subsequent reduction in blood feeding. Further work is needed to quantify this phenomenon and other indirect fitness consequences of LLIN exposure in IR mosquitoes to calculate their combined impact on transmission (13).…”
Section: Discussionmentioning
confidence: 99%
“…En las pruebas con los insecticidas deltametrina y lambdacialotrina, al finalizar el tiempo de exposición y retirar las hembras de L. longipalpis, se observó un gran número de patas desprendidas en la superficie de la botella, efecto que se ha observado en otros estudios tras la exposición de esta especie a los piretroides (20,30).…”
Section: Resultsunclassified
“…En Venezuela, Mazzari, et al (19), detectaron mayores tiempos letales medios (TL 50 ) en los insecticidas metilpirimifos, fenitrotión y permetrina en una población de L. longipalpis expuesta a insecticidas con propósitos agrícolas, comparada con una cepa sensible de laboratorio. En Brasil se registraron valores de TL 50 para los piretroides permetrina y deltametrina, significativamente más altos en una población de L. longipalpis expuesta frecuentemente a piretroides para el control de la leishmaniasis visceral que los encontrados en una población de L. longipalpis geográficamente distante y sin evidencia de exposición a insecticidas, lo que se confirmó con análisis bioquímicos de la actividad de las enzimas de desintoxicación de insecticidas (20).…”
unclassified